Kontrol diri pada perilaku konsumtif remaja yang menggunakan fitur Shopee Pay Later - Fuadi, Robeth; Supraba, Dellawaty (UIN Maulana Malik Ibrahim Malang, 2023)
This study aims to explain the effect of self-control on the consumptive behaviour of teenagers who use the Spaylater feature. This study uses a quantitative research design. The population in this study are teenagers who use the Spaylater feature and are not known with certainty (infinite population). The sample taken amounted to 140 teenage respondents who used the Spaylater feature. This sampling technique uses an accidental sampling technique. Based on the results of hypothesis testing, self-control has a significant effect on consumptive behaviour. This study shows the self-control variable's coefficient of determination for adolescent Spaylater users' consumptive behaviour. These results indicate that self-control has an influence of 47% on the consumptive behaviour of adolescent Spaylater users. In contrast, other factors not mentioned in this study influence the restKEY WORDS: self-control; consumptive behavior; adolescent; shopee payABSTRAKPenelitian ini bertujuan untuk memaparkan pengaruh kontrol diri terhadap perilaku konsumtif remaja yang menggunakan fitur Spaylater. Penelitian ini menggunakan desain penelitian kuantitatif. Populasi dalam penelitian ini adalah remaja yang menggunakan fitur Spaylater dan tidak diketahui secara pasti (populasi infinite). Sampel yang diambil berjumlah 140 responden remaja yang menggunakan fitur Spaylater. Pengambilan sampel ini menggunakan teknik accidental sampling. Berdasarkan hasil uji hipotesis, kontrol diri berpengaruh signifikan terhadap perilaku konsumtif. Berdasarkan hasil analisis data penelitian ini menunjukkan koefisien determinan variabel kontrol diri (R-Square) untuk perilaku konsumtif remaja pengguna Spaylater. Hasil ini menunjukan bahwa kontrol diri memiliki pengaruh sebesar 47% terhadap perilaku konsumtif remaja pengguna Spaylater, sedangkan sisanya dipengaruhi oleh faktor lain yang tidak disebutkan dalam penelitian ini.KATA KUNCIkontrol diri; perilaku konsumtif; remaja: shopee pay Copyright ©2023. The Authors. Published by Journal of Indonesian Psychological Science (JIPS). This is an open access article under the CC BY NO SA. link: Creative Commons — Attribution-NonCommercial-ShareAlike 4.0 International — CC BY-NC-SA 4.0